Implementation of electronic throttle-by-wire for a hybrid electric vehicle using National Instruments' CompactRIO and LabVIEW Real-Time - Zulkifli, S.A. (IEEE Computer Society, 2014)
A vehicle propulsion system based on internal combustion engine (ICE) includes a throttle body whose function is to regulate the amount of air-fuel intake into the engine to vary the engine's power and thus vehicle acceleration. A mechanical throttle valve body attached to the ICE's air intake manifold is linked to the driver's accelerator pedal via mechanical cable. An alternative system is based on an electronic throttle: an electromechanical device controlled electronically by power transistors. Coupled with an accelerator pedal and a built-in position sensor, the system is referred to as an electronic throttle-by-wire (TBW). This paper describes implementation of an electronic TBW in a conversion hybrid electric vehicle. It explains components and sub-systems of the TBW and application of a closed-loop throttle position control. The controller used is an embedded CompactRIO controller from National Instruments, programmed with LabVIEW Real-Time. Bench testing of the TBW and throttle position control system is presented. Â© 2014 IEEE.